Bleeder : A Memoir - Smoak, Shelby (Book collections on Project MUSE., 2013)
The author, a hemophiliac, discovered he had been infected with HIV during a blood transfusion at the start of his college career. This devastating and destabilizing news led the author to see his world from an entirely new perspective, one in which life-threatening illness was perpetually just around the corner. Set in the 1990s along the North Carolina coast, the book traces his quest for love in a world that feels increasingly dangerous, and despite a future that feels increasingly uncertain. From the bedroom to the operating room, and from one hospital to the next, the author seeks out hope and better health.